Pharmacoeconomic analysis of type 2 diabetes mellitus by vildagliptin medication in Kazakhstan - Yelekenova, A.; Bektur, C.; Nurgozhin, T. (Nazarbayev University, 2014)
This study is aimed to determine cost-effectiveness of vildagliptin in comparison with sitagliptin for the treatment of patients with type 2 diabetes mellitus (T2DM) from the perspective of Ministry of Health of the Republic of Kazakhstan.
Keywords: pharmacoeconomic; analysis; diabetes; metformin; therapy